Species richness of vascular plants, butterflies and bumblebees in linear infrastructure habitats and the historical and present grassland cover in a 2 km buffer surrounding each habitat - Horstmann, Svenja (Swedish University of Agricultural Sciences, 2023)
This data set comprises the species richness of vascular plants, butterflies and bumblebees in linear infrastructure habitats (road verges and power lines) and the historical and present grassland cover in a 2 km buffer surrounding each habitat.

The main purpose of this data set is to investigate if older linear infrastructure habitats sustain a higher richness of vascular plants and pollinators, and to study if the surrounding grassland habitat in the landscape from the past or the present has an influence on the contemporary species richness. The data also contains the species richness of grassland specialist vascular plants and butterflies, which is a subset from the total richness of the respective groups.

The data on plants and pollinators was assessed during fieldwork in 2016. The data on grassland cover was calculated using the Swedish National Land Cover Data (NMD, Nationella marktäckedata) for the contemporary grassland, and a digitized Swedish Economic Map from the 1950s.

The dataset consists of 112 rows and 15 columns, excluding headers. Each row contains information for one studied habitat (112 in total). The columns contain information on the studied 'Landscape' and 'Habitat' within the landscape, the coordinates of the transect in each habitat ('Start_X', 'Start_Y', 'End_X', End_Y'), information on the time since habitat establishment ('FirstAppearance') and the surrouding grassland cover in the past and present ('1950s_Grassland' and '2017_Grassland', respectively), and the continuously existing grassland ('Continuous_Grassland'). Furthermore, it contains information on the species richness of all vascular plants ('PL_rich_all') and grassland specialist vascular plants ('PL_rich_spec'), all butterflies ('BF_rich_all') and grassland specialist butterflies ('BF_rich_spec'), and bumblebees ('BB_rich').

For further explanation on the information and how it was assessed, please see the README file.

Dessa data beskriver artrikedom av växter, dagfjärilar och humlor i linjära infrastrukturmiljöer (vägkanter och kraftledningar), och historisk och nutida täckning av gräsmarker i en 2 km buffert runt respektive plats.

Se engelsk beskrivning för mer detaljerad information.

Datamängden består av 112 rader och 15 kolumner, exklusive rubriker. Varje rad innehåller information om en studerad habitat (totalt 112). Se den engelska informationen för en beskrivning av informationen i varje kolumn.
Artrikedom av växter, dagfjärilar och humlor i linjära infrastrukturmiljöer, och historisk och nutida täckning av gräsmarker i en 2 km-buffert runt respektive plats.
Keywords: road verges; vägrenar; electric power lines; ellinjer; bumblebees; humlor; Lepidoptera; fjärilar; vascular plants; kärlväxter; grasslands; gräsplaner; tracheophyta; apidae; lepidoptera; linear infrastructure habitats; linjära infrastrukturmiljöer; Ecology; Ekologi